Resource Design of Structural Concrete Berthing Structures Based on Tribo-Fatigue Methods - S. N. Leonovich; С. Н. Леонович (Belarusian National Technical University, 2025)
An increase in one or another damaging factor leads to a decrease in strength or wear resistance. The interaction of damaging phenomena turns out to be complex. If contact load (friction and wear) is added to cyclic loading or cyclic freeze-thaw (mechanical fatigue), then the reliability and durability of the system receiving them can either decrease, increase, or remain at the same level. The results depend on the conditions of interaction of damaging phenomena. At the intersection of tribology and mechanics of fatigue fracture in the mid-1980s, thanks to the research of Professor Sosnovsky L.A., tribo-fatigue arose – a science that studies not the mutual influence of individual damaging factors, but a complex combination of various damaging phenomena. As a result of this interaction, a special type of degradation of structural concrete of berthing structures is revealed – complex wear-fatigue damage. The conditions and patterns of such damage to berthing structures are studied by tribo-fatigue. Design of reinforced concrete structures based on limit states is a traditional method. For critical structures of berth structures, resource-based design is advisable. Technical resource is an indicator of durability. This is the operating time of an object, in this case reinforced concrete berth structures, from the start of operation until the onset of the limit state. Sea port facilities on the coast of the Far Eastern seas, a distinctive feature of their operation being the climatic conditions of Sakhalin Island, have been studied. The structures of port facilities are affected by waves. In winter, when the temperature drops to below zero, structures become icy in variable water levels and are affected by floating ice. Усиление того или иного повреждающего фактора ведет к снижению прочности, или износостойкости. Взаимодействие повреждающих явлений оказывается сложным. Если к циклической нагрузке (циклическое замораживание-оттаивание, механическая усталость) добавить контактную нагрузку (трение и износ), то ...